2008
DOI: 10.1093/bmb/ldn002
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve: a literature review and its impact on sport activity

Abstract: The bicuspid aortic valve (BAV) is the most common congenital cardiac malformation. A literature search was performed using the key words 'bicuspid aortic valve', 'pathophysiology', 'exercise' and 'training'. BAV is the result of a complex developmental process where several genes seem to lead to abnormal valvulogenesis. Complications associated with BAV include aortic stenosis (AS) and regurgitation, infective endocarditis and aortic dilation and dissection. Moreover, BAV may be associated with other cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 85 publications
3
29
0
8
Order By: Relevance
“…In athletes, competitive sports activity is normally allowed if the valve dysfunction or the other complications associated are not severe [9, 16]. Some aspects remain unsolved, especially in athletes who train regularly.…”
Section: Discussionmentioning
confidence: 99%
“…In athletes, competitive sports activity is normally allowed if the valve dysfunction or the other complications associated are not severe [9, 16]. Some aspects remain unsolved, especially in athletes who train regularly.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its seemingly low incidence, the BAV is responsible for causing more valvular and vascular disease compared to all other congenital heart defects combined [4] . Unlike the normal tricuspid aortic valve (TAV) which consists of three leaflets, the BAV forms with only two [5][6][7] . While there are different BAV morphogenic phenotypes [8][9][10] , the most common is referred to as the type-I BAV and is characterized by the presence of two cusps of unequal size and one fibrous raphe marking the site of fusion on the larger leaflet [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Even though there may be an increased risk of aortic dissection during pregnancy, three studies of a small number of pregnant women with Turner syndrome actually found no cases of aortic dissection or rupture (11). In fact, the natural evolution of bicuspid aortic valve is not completely clear even for men engaged in strenuous sporting activities (12). On the basis of aortic dissection observations in a patient with normal ascending aortic diameter, others suggested that pregnancy is contraindicated in patients with Turner syndrome with normal aortic diameter (13).…”
Section: Discussionmentioning
confidence: 99%